Chronotope, Water Law and Rurality. Unraveling the challenges of implementing the Chilean Rural Sanitation Services Law - Nicolas-Artero, Chloé (Investigaciones Geográficas: Una mirada desde el sur, 2024)
This study analyzes the regulatory shift that has occurred due to the implementation of the Chilean Rural Sanitation Services Law from a legal geographic perspective. How do the protagonists of the law’s relationship with time and space affect the speed of such regulatory transition? This paper, based on a mixed methodology proposed to analyze law in action, demonstrates how the conflicting temporalities of lawmakers, officials from the Superintendence of Sanitation Services (SISS), and leaders of Rural Sanitation Services (RSS) impede this regulatory transition and alter its objectives by (re)producing heterogeneous ways of distributing drinking water.